Breast cancer screening effectiveness in Portugal central Region. (September 2017) - Bastos, Joana; Rodrigues, Vitor; Paap, Ellen; Broeders, Mireille; Pina, Miguel; Cruz, Dário; Carrito, Branca; António Silva, Manuel
Abstract : The central region of Portugal is covered by an organized population-based breast cancer screening programme. We designed a case-referent study to investigate the association of overall mortality with mammographic screening attendance. The study population (SP) included women aged 50–69 years who received at least one invitation to the breast cancer screening programme. A case was defined as a woman from the SP diagnosed with breast cancer between 2000 and 2006 who died before 1 August 2015. Index invitation (IV) was defined as the most recent invitation before diagnosis of the case. For each case, two referents were sampled from the SP. Referents were women who did not have a breast cancer diagnosis at the IV of the case and alive at time of death of the case. Exposure to screening was defined as participation in the screening examination following the IV and/or participation in the screening round preceding the IV. To correct for self-selection bias, we used a summary correction factor on the basis of published ones. We used conditional logistic regression to estimate the odds ratio (OR) and 95% confidence interval (CI). A total of 227 cases and 454 referents were considered. The overall OR showed a mortality reduction of 47% (OR=0.53, 95% CI: 0.37–0.78). The estimated correction factor was 1.15 (95% CI: 1.06–1.25). This factor was used to correct the crude OR, resulting in a mortality reduction of 33% (OR=0.67, 95% CI: 0.45–1.00). Our results are in agreement with other case-referent studies worldwide, supporting the contribution of screening practices towards the decreasing breast cancer mortality in Portugal.